Influence of substratum position and acquired pellicle on Candida albicans biofilm - Indira Moraes Gomes Cavalcanti; Wander José da Silva; Silvia Carneiro de Lucena; Camila Cordeiro Pousa; Altair Antoninha Del Bel Cury (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The purpose of this study was to evaluate the influence of the substratum position and the saliva acquired pellicle (AP) on Candida albicans biofilm development. Poly(methylmethacrylate) (PMMA) disks were fabricated and randomly allocated to experimental groups: HNP (disks placed in a horizontal position and uncoated by pellicle), VNP (disks placed in a vertical position and uncoated by pellicle), HCP (disks placed in a horizontal position and coated by pellicle), and VCP (disks placed in a vertical position and coated by pellicle). Disks were placed in a 24-well plate and a suspension of 107 cells/mL of Candida albicans was added to each well for biofilm development. The plates were aerobically incubated at 35°C. The biofilms were evaluated at 1.5 (adhesion time point), 24, 48, 72, and 96 hours. The number of viable cells was quantified in terms of the colony-forming units per milliliter (CFU/mL). Metabolic activity was measured by the XTT assay. The biofilm structure was analyzed by scanning electron microscopy. The data were analyzed by three-way ANOVA followed by Tukey's test, with significance set at 5%. The vertical groups showed less biofilm formation and lower metabolic activity than the horizontal groups (p< 0.05). Significant differences in cell viability and metabolic activity were observed between the adhesion and other time points (p< 0.05), but these variables were not affected by the presence of the pellicle (p > 0.05). It can be concluded that the substratum position influenced biofilm development.